Evaluation of selected seed treatment methods for the control of Fusarium graminearum and F. avenaceum on wheat seeds - Anna, K. M. (International Journal of Agricultural Technology, 2016)
Seed-borne diseases cause serious yield in cereal crop production in Lesotho, especially under small-holder farming systems. The main aim of the sudy was to determine the occurrence of both F. graminearum and F. avenaceum from different areas in Lesotho and evaluate the effect of various control measures on pathogen growth in vitro and disease incidence under green house conditions. Both F. graminearum and F. avenaceum were present in all four wheat cultivars irrespective of their area of collection. Various control measures were applied to determine their efficacy in suppressing pathogen growth in vitro, effect on seed germination and disease incidence under greenhouse conditions. The three tested plant extracts and Thiram significantly reduced mycelial growth of both pathogens and showed no negative effect on seed germination with Thiram exhibiting 100% pathogen growth inhibition. Hot water treatment of farm saved wheat seeds also resulted in an increased number of germinated seeds and reduced number of diseased wheat seedlings when compared with control. The lowest germination percentage was recorded in non-treated seeds where only 5.3% Eland seeds germinated. Results obtained in this study show that the three tested plant extracts and hot water treatement can be used to control wheat seed infestation by the two Fusarium spp and improve seed germination.